Teens and jeans : clothing in transition - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
Denim and jeans are consistently popular in most countries throughout the world. However, despite their universal appeal, different markets result in different brands and denim styles being more popular in some countries than others. This case study examines the international jeans market, particularly among teenagers.